Inovasi Kurikulum Madrasah di Pesantren Kabupaten Banyuwangi dalam Mengimplementasikan Civic Education - Moh. Harun Al Rosid; Eko Budiywono; Mamlukhah Mamlukhah (IAI Darussalam, 2018)
Reasons for Choosing Side-by-Side, namely: (1) Madrasas need curriculum innovations in order to contribute to the success of madrasa goals that are in line with the objectives of national education; (2) Madrasas have never received civic education assistance from the Banyuwangi district government; (3) Madrasah students need an understanding of civic education, especially insight into the archipelago as a counterweight to understanding religion and nation in the Unitary State of the Republic of Indonesia for the provision of living in a pluralistic society. The approach used is Participatory Action Research (PAR). The conclusion obtained from the results of this service is that the madrasah curriculum innovation at the pesantren is important, given that Islamic religious education at the pesantren contributes greatly to the Republic of Indonesia as a moral fortress as well as a stronghold of radicalism. Positive responses and stakeholder support are also a great motivation for the smoothness and success of the madrasah-based community service program carried out at the largest madrasah diniyah in Banyuwangi district, hoping that it could become a reference and barometer for the madrasah diniyah in Banyuwangi district